2011
DOI: 10.1515/ijamh.2011.057
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare utilization for pain in children and adolescents: a prospective study of laboratory and non-laboratory predictors of care-seeking

Abstract: Background-Few studies have focused on identifying predictors of medical consultation for pain in healthy children and adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…This development with age is reflected in pain assessment, where for children under the age of 6, behavioural pain scales are usually needed to assess pain, whereas for older children pain assessment can be based on self-report and several self-reporting tools are also recommended from the age of 4 (Beltramini, Milojevic, & Pateron, 2017). Studies have reported that parents with poorer health status (Dreyer, Williamson, Hargreaves, Rosen, & Deeny, 2018;Tsao, Evans, Seidman, & Zeltzer, 2011), or who are high healthcare users themselves (Zhang, Zhou, & Si, 2017), were more likely to seek healthcare for their children. This indicates that parents could play an important role in patterns of healthcare consultation.…”
Section: Discussionmentioning
confidence: 99%
“…This development with age is reflected in pain assessment, where for children under the age of 6, behavioural pain scales are usually needed to assess pain, whereas for older children pain assessment can be based on self-report and several self-reporting tools are also recommended from the age of 4 (Beltramini, Milojevic, & Pateron, 2017). Studies have reported that parents with poorer health status (Dreyer, Williamson, Hargreaves, Rosen, & Deeny, 2018;Tsao, Evans, Seidman, & Zeltzer, 2011), or who are high healthcare users themselves (Zhang, Zhou, & Si, 2017), were more likely to seek healthcare for their children. This indicates that parents could play an important role in patterns of healthcare consultation.…”
Section: Discussionmentioning
confidence: 99%
“…162 In addition, dietary interventions have been shown to reduce pain in adults with irritable bowel syndrome, 55 and pain and psychological distress in adults with headache, 110 suggesting that diet and nutrition habits within a family might influence pain outcomes. Health care utilization may also play a role, as parental health status has been associated with pain-related medical visits in children, 141 and mother and child health care visit frequency are positively correlated in families in which the mother has irritable bowel syndrome. 146 Families who catastrophize about pain may be more likely to seek frequent medical care which, in turn, may further increase pain catastrophizing.…”
Section: Potential Mechanisms For the Transmission Of Riskmentioning
confidence: 99%
“…Despite there being evidence that a child's appraisal of a situation is likely to impact on their subsequent behavior, 18 as well as their memory of the experience, 19 within the clinical pediatric acute pain context, children's appraisals are rarely assessed is a standardized way. Nevertheless, aspects of appraisal, such as how bothersome the painful experience is, [20][21][22] and belief in one's ability to cope with the painful experience, are likely to hold particular salience for the individual and may be of greater personal importance than the degree of sensory intensity.…”
mentioning
confidence: 99%